Motnje čutilnih in prepoznavnih sposobnosti pri otrocih in njihov pomen v razvoju otroka - Groleger, Katja (Rehabilitacija (Ljubljana), 2012)
The article summarizes the facts about the development of sensory systems, the importance of critical periods for the development of perception, and about the development of focused attention and sensory processing. Those processes are very complex and the child only gradually develops the abilities under various influences, including genes and the environment. In case of perception dysfunction in children, functioning - movement, speech and communication skills, behaviour and emotions - is also changed. It is becoming evident that an enriched environment allows more successful development of perception, which might be the basis for therapeutic programs aimed at reducing sensory dysfunction and improving functioning abilities of children.
Keywords: Child; development; motnje občutenja; otroci; percepcija; Perception; razvoj; sensory dysfunction; zaznavanje